Indigenous cultural heritage policies as a pathway for Indigenous sovereignty and the role of local governments: an example with K'ómoks First Nation, British Columbia - Kelly, Mary; Morin, Jesse; Tarle, Lia; Newman, Candace; Bevilacqua, Raini; Barnett, Sheriden; Markey, Sean; Lepofsky, Dana (Frontiers in Environmental Archaeology, 2024)
Indigenous cultural heritage (ICH) is threatened worldwide, driven by factors like development, private property rights, and colonial planning. Indigenous communities are increasingly navigating the inadequacies of ICH protection by exerting their rights through laws, protocols, and policies. These initiatives assert sovereignty and relational responsibility to ancestral cultural heritage outside of the mandated colonial systems of management. This study centers on the Comox Valley in British Columbia, where the ICH of K'ómoks First Nation is under increasing threat of erasure due to private and commercial development. In response, the K'omoks First Nation has developed their own Cultural Heritage Policy (CHP), and accompanying archaeological permits to protect their cultural heritage where provincial archaeological legislation fails to. In the context of the K'omoks First Nation, we explore three interconnected questions associated with the assertion of Indigenous Peoples' rights and responsibilities around protecting their ICH: how do Indigenous communities exert self-determination over their ICH, how does ICH interact with local planning processes, and how can local (settler) governments strengthen ICH protection at the local level? Our findings reveal that local level implementation of Indigenous cultural heritage policies help to ensure that ICH protection strategies are effective and meet the needs of Indigenous Indigenous communities. Challenges remain, however, regarding jurisdictional barriers to formal policy adoption within the colonial regulatory regime, capacity limitations, and the need for public education and communications regarding Indigenous-led heritage policies.